Less is more: Qualitative insights into physically active learning in secondary math education - María González-Pérez; Alberto Grao-Cruces; Francisco J. Bandera-Campos; Anna Chalkley; Daniel Camiletti-Moirón; David Sánchez-Oliva (PLoS ONE, 2025)
Background Physically active learning (PAL) has shown promise as a pedagogical approach that combines physical and academic benefits by incorporating physical activity during academic lessons. However, its implementation in secondary schools remains a challenge, highlighting the need to explore teachers’ and students’ perceptions and experiences. Aim To assess the perceptions and experiences of teachers and students following their participation in a PAL intervention in secondary education. Methods Data were collected through individual interviews with mathematics teachers (n = 5) and six focus groups with students (n = 36) who participated in a 16-week intervention with a weekly outdoor PAL lesson. Data were analyzed using conventional content analysis. Results Teachers reported a general increase in students’ motivation. They also noted an improvement in the participation and behavior of some students during PAL lessons. These aspects were also reported by the students themselves. Although teachers and students perceived that the amount of content covered in a PAL lesson was lower compared to traditional lessons, they emphasized that learning was more meaningful due to enhanced retention, facilitated by active engagement and dynamic teaching approaches. Teachers and students also perceived an improvement in students’ cooperation and socialization. Teachers considered PAL to be a feasible pedagogical approach to implement, provided adequate resources were available. Conclusions PAL is seen as a pedagogical approach that brings both social and academic benefits to secondary education. However, to ensure its effectiveness and long-term sustainability, it needs to be integrated into the whole educational community.